Building User Manual : A Vital Component Of The Malaysian Green Building Index - Nurakmal, Abdullah@ Goh Tuo Ho; Mohd Nurfaisal, Baharuddin; Che-Ani, A. I.; Mazlan, Mohd Tahir; Norngainy, Mohd Tawil; Utaberta, Nangkula (2011)
The provision of decent and well-maintained buildings is one of the visions of developers and contractors in Malaysia. Most modern buildings and infrastructure contain new and innovative features that have been introduced into our built asset. Compared with national economic projections, this shows unexpected improvement, especially regarding issues of development and infrastructure. However, the high demand for new construction, including residential and multi-purpose buildings such as office buildings and government buildings, requires the government and the private sector to provide guidelines and procedures to ensure that the buildings will be economical in terms of life cycle costs. For this reason, a comprehensive approach is necessary for the management of the assets and facilities. The introduction of a Green Building Index, which implements an inclusive and holistic approach to building management, is a good idea and a concept that will be beneficial to Malaysian people. The development of the Building User Manual as one of the criteria that must be completed by developers, as in line with the requirement of Malaysian Green Building Index. This paper provides a systematic discussion of the various documents involved in developing the Building User Manual.